2021
DOI: 10.1038/s41598-021-94605-7
|View full text |Cite
|
Sign up to set email alerts
|

Corneal inflammatory cell infiltration predicts disease activity in chronic inflammatory demyelinating polyneuropathy

Abstract: The assessment of disease activity is fundamental in the management of chronic inflammatory demyelinating polyneuropathy (CIDP). Previous studies with small patient numbers found an increase of corneal immune cell infiltrates as a potential marker of inflammation in patients with CIDP. However, its clinical relevance remained unclear. The present study aimed to determine whether the amount of corneal inflammatory cells (CIC) measured by corneal confocal microscopy (CCM) detects disease activity in CIDP. CIC we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Two subsequent longitudinal studies in CIDP have shown that increased corneal inflammatory cells can predict disease progression with high sensitivity. 41 42 Kemp et al 43 showed a loss of corneal nerve fibers in patients with HIV-associated neuropathy, and we further showed that the corneal nerve fractal dimension might differentiate HIV neuropathy from diabetic neuropathy. 44 Idiopathic small fiber neuropathy is characterized by painful neuropathic symptoms and small fiber dysfunction/damage with preserved large fiber function 45 ; we have shown a significant loss of corneal nerves in patients with idiopathic small fiber neuropathy 46 with an increased detection rate of this condition using CCM.…”
Section: Ccm In Other Peripheral Neuropathiessupporting
confidence: 69%
“…Two subsequent longitudinal studies in CIDP have shown that increased corneal inflammatory cells can predict disease progression with high sensitivity. 41 42 Kemp et al 43 showed a loss of corneal nerve fibers in patients with HIV-associated neuropathy, and we further showed that the corneal nerve fractal dimension might differentiate HIV neuropathy from diabetic neuropathy. 44 Idiopathic small fiber neuropathy is characterized by painful neuropathic symptoms and small fiber dysfunction/damage with preserved large fiber function 45 ; we have shown a significant loss of corneal nerves in patients with idiopathic small fiber neuropathy 46 with an increased detection rate of this condition using CCM.…”
Section: Ccm In Other Peripheral Neuropathiessupporting
confidence: 69%
“…In patients with CIDP, a baseline IC count >30 cells/mm 2 had a 100% sensitivity for predicting disease progression over 6 months. 47 In MS, we have previously shown a significant increase in dendritic cells over 2 years in smaller sample of patients with RRMS, 16 while others have recently reported no change in remitting patients over 6 months. 48 In the present study, our results at follow-up suggest that both dendritic and non-dendritic cells undergo dynamic alterations, particularly in RRMS, Increased corneal IC density has been inversely correlated with reduced corneal nerve density 49 in patients with bacterial keratitis and has been related to increased levels of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 93%
“…Our group was the the first to show increased LC’s in patients with chronic inflammatory demyelinating polyneuropathy (CIDP), suggesting that corneal LC’s may be a surrogate marker of antigen presenting cell status in peripheral nerves 22 . Indeed, recent studies in patients with CIDP have shown that increased LC’s may predict increased rates of disease progression and neurological disability 23 , 24 . Furthermore, treatment of a 27-year-old patient with subacute anti-neurofascin-155 neuropathy with rituximab was associated with an improvement in clinical and neurophysiological parameters and a reduction in antibody titers and LC density 25 .…”
Section: Discussionmentioning
confidence: 99%